Prenatally Diagnosed Infant AML. Issue 3 (April 2018) - Schlosser, Mary-Pat; Bucking, Shannon; Lemyre, Brigitte; Grynspan, David; Padmore, Ruth; Johnston, Donna
Abstract : We report the first case of a fetus with acute myeloid leukemia, without Down syndrome, diagnosed in utero. A cordocentesis sample prepared to investigate hepatomegaly led to further evaluations revealing acute myeloid leukemia, monocytic type, in the fetus. Cytogenetic analysis showed mixed lineage leukemia duplication, no gene disruption or trisomy. Planned treatment included intrauterine exchange transfusion to extend gestation, low-dose chemotherapy at birth, and full chemotherapy once stable. Before any intervention, the child was delivered emergently for maternal condition and died 2 hours later. Although it is now possible to diagnose hematologic malignancy in a fetus, there is little information to direct management.